Wild target [videorecording (DVD)] - Nighy, Bill, 1949-; Blunt, Emily; Freeman, Martin, 1971-; Grint, Rupert, 1988- (Samuel Goldwyn Films, 2024)
A hitman tries to retire, but a beautiful thief may change his plans.